Development and optimization of a differentiated airway epithelial cell model of the bovine respiratory tract - Cozens, Daniel; Grahame, Edward; Sutherland, Erin; Taylor, Geraldine; Berry, Catherine C.; Davies, Robert L. (Scientific reports, 2018)
Cattle are subject to economically-important respiratory tract infections by various bacterial and viral pathogens and there is an urgent need for the development of more realistic in vitro models of the bovine respiratory tract to improve our knowledge of disease pathogenesis. In the present study, we have optimized the culture conditions in serum-free medium that allow bovine bronchial epithelial cells (BBECs) grown at an air-liquid interface to differentiate into a three-dimensional epithelium that is highly representative of the bovine airway. Epidermal growth factor was required to trigger both proliferation and differentiation of BBECs whilst retinoic acid was also essential for mucociliary differentiation. Triiodothyronine was demonstrated not to be important for the differentiation of BBECs. Oxygen concentration had a minimal effect although optimal ciliation was achieved when BBECs were cultured at 14% oxygen tension. Insert pore-density had a significant effect on the growth and differentiation of BBECs; a high-pore-density was required to trigger optimum differentiation. The established BBEC model will have wide-ranging applications for the study of bacterial and viral infections of the bovine respiratory tract; it will contribute to the development of improved vaccines and therapeutics and will reduce the use of cattle in in vivo experimentation.